2013
DOI: 10.1371/journal.pone.0079850
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Surface Mucus-Binding Protein and Pili in Muco-Adhesion of Lactococcus lactis

Abstract: Adhesion of bacteria to mucus may favor their persistence within the gut and their beneficial effects to the host. Interactions between pig gastric mucin (PGM) and a natural isolate of Lactococcus lactis (TIL448) were measured at the single-cell scale and under static conditions, using atomic force microscopy (AFM). In parallel, these interactions were monitored at the bacterial population level and under shear flow. AFM experiments with a L. lactis cell-probe and a PGM-coated surface revealed a high proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 49 publications
3
54
1
Order By: Relevance
“…This model is consistent with the previous interpretations of Gram-negative pili structure [87][88][89]. In a similar study, strains of Lactococcus lactis were immobilized onto polyethyleneimine (PEI)-coated cantilever, and adhesion to a pig gastric mucin-coated substrate was characterized [90]. In the study, long-range adhesion was found to be predominantly the result of pili-mediated binding, while surface adhesion was primarily mediated by mucus-binding adhesins.…”
Section: Single-cell Force Spectroscopysupporting
confidence: 89%
“…This model is consistent with the previous interpretations of Gram-negative pili structure [87][88][89]. In a similar study, strains of Lactococcus lactis were immobilized onto polyethyleneimine (PEI)-coated cantilever, and adhesion to a pig gastric mucin-coated substrate was characterized [90]. In the study, long-range adhesion was found to be predominantly the result of pili-mediated binding, while surface adhesion was primarily mediated by mucus-binding adhesins.…”
Section: Single-cell Force Spectroscopysupporting
confidence: 89%
“…To support the second option, the functionality of L. lactis cell wall proteins was assessed in vivo using a ∆ srtA mutant [74]. Consistent with these data, the presence of various gene clusters associated with pili biogenesis, their efficient expression—for instance—in the plant TIL448 strain [57] and the ability to adhere to mucin, also conferred by the joint expression of a mucus-binding protein [58], reinforce lactococcal adhesion as a pivotal factor in transient persistence of L. lactis in the gut. Intestinal growth of L. lactis may also be a key parameter for increased fitness in the intestine.…”
Section: Technical and Specific Properties Of Environmental Strainmentioning
confidence: 99%
“…A recent publication described a CRISPR-Cas system that was encoded by a lactococcal plasmid, although it was concluded not to be functional [20]. In addition, several genes related to lactococcal surface properties are carried on plasmids [2123], such as aggL , a gene responsible for cell auto-aggregation, or genes responsible for adhesion to mucus [24]. …”
Section: Introductionmentioning
confidence: 99%
“…lactis strains also express proteinaceous surface appendages called pili [21,22,24]. Pili are known to have different functions in bacteria, including adhesion to surfaces (type I pili) or motility (type IV pili) [3639].…”
Section: Introductionmentioning
confidence: 99%